Analisa Receiver Function Teleseismic untuk Mendeteksi Moho pada Stasiun Bkb Data Meramex - Rian Amukti; Wiwit Suryanto (Department of Physics, Sebelas Maret University, 2016)
It has been done a research to determine internal earth using receiver function teleseismic analysis method. This method have been done by using MERAMEX (MErapi Amphibious Experiment) data from broadband seismometer BKB. Event of teleseismic is chosen from Honshu Japan with radius 30o and magnitude 7.2. This research begun by analysing radial and vertical characteristic of teleseismic eventand using bandpass filter with range 0.003 Hz – 0.5 Hz. Then Iteractive Deconvolution is used to get velocity model. The result of this model shows crustal model that has 4 Km thick upper crust, a 26 Km thick lower crust and 10 Km thick Moho transition zone, with velocity increasing gradually.